Developing an University Immersive Campus: Guidelines for Beginner Developers - Brito, Gabriel de; Scheltes, Danilo; Durval, Anna; Aragão, José; Santos, Sanval Ebert; Lima, Cláudia; Soussa, Márcio; Winkler, Ingrid (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2024: Anais do XXVI Simpósio de Realidade Virtual e Aumentada, 2024)
Immersive campuses are becoming an increasingly prevalent trend in how universities interact with their academic community and technologies like the metaverse emerge as promising resources to enhance the educational experience. The metaverse can provide more engaging and interactive learning experiences, allowing students to explore information in a practical and immersive way. This study provides guidelines for beginner developers creating immersive campuses for exploring a university. Using the design science research approach, we developed a three-stage simulation with progressive challenges and interactions in the Unity game engine and Meta Quest 2 device. Then an exploratory group evaluated the potential user acceptance and usage with the UTAUT2 model and we finally carried out a focus group. The results indicated that the immersive Campus was perceived as easy and enjoyable to use, though recommendations were not a major influence for most users. This discrepancy may have led many participants to disagree that influential individuals believed they should use the tools. Despite this, participants expressed an intention to utilize RV authoring tools in the future, albeit without a commitment to regular usage. We compiled seven guidelines, including prioritizing seated immersive experiences, enhancing visual accessibility, optimizing code post-update, organizing interface components, using progressive loading for responsiveness, and optimizing texture loading functions to prevent performance issues, among others.